The Novel Compound Heterozygous Mutations in the AGL Gene in a Chinese Family With Adult Late-Onset Glycogen Storage Disease Type IIIa - Qu, Qianqian; Qian, Qi; Shi, Jiejing; Liu, Haiyan; Zhang, Yan; Cui, Wenhao; Chen, Ping; Lv, Haidong (Frontiers in Neurology, 2020)
Objective: Glycogen storage disease type III (GSD III) is a rare autosomal recessive genetic disorder that is caused by a deficiency of the glycogen debranching enzyme. In most cases, GSD III is diagnosed in childhood; late-onset GSD III in adults is rarely reported. This study focused on a Chinese family with adult late-onset GSD IIIa and investigated their clinical features, magnetic resonance imaging (MRI) findings, and pathological changes in the muscle. We also carried out genetic analysis to investigate the presence of mutations. Methods: The proband is a 40-year-old male who was admitted into our hospital on the 21st of November 2019 with a 15-year history of elevated muscle enzymes and a two-year history of limb weakness. The muscle tension in both upper and lower limbs was low, and tendon reflexes were absent. The proband’s muscle strength was graded as 3-5 in his limbs. Next, we performed neuroelectrophysiological examinations, muscle MRI, and muscle biopsy. We also extracted DNA from blood samples collected from the proband and his direct family (parents and older brother), and used this DNA to test for AGL mutations. Results: MRI revealed abnormally high signal intensity changes in the posterior compartment muscles of both upper legs, and the posterior-medial compartment of both lower legs. Vacuoles were evident in some muscle fibers. Periodic acid-Schiff staining stained the cytoplasm of muscle fibers a dark red color. The proband's older brother exhibited the same clinical symptoms. DNA analysis identified mutations in the AGL gene in the proband, his parents, and his older brother. The proband and his older brother both carried two compound heterozygous mutations, c.866G>A and c.2855_2856insT. Pedigree analysis further verified that the c.866G>A and c.2855_2856insT mutations had been inherited from the mother and father, respectively. Conclusion: Adult onset GSD IIIa is clinically characterized by muscle weakness, muscle atrophy, and an elevation in the concentrations of muscle enzymes. In both cases in the present study, the strongest effects were observed in the posterior compartment muscles of the lower extremities. We also identified two novel compound heterozygous mutations (c.866G> A and c.2855_2856insT) in the AGL gene.